Mechanism of the inhibition of leukemia cell growth and induction of apoptosis through the activation of ATR and PTEN by the topoisomerase inhibitor 3EZ, 20Ac-ingenol. Issue 9 (September 2015) - Miyata, Shohei; Fukuda, Yasuaki; Tojima, Haruka; Matsuzaki, Keiichi; Kitanaka, Susumu; Sawada, Hiroshi
Highlights 3EZ, 20Ac-ingenol showed characteristics as a topoisomerase catalytic inhibitor, inducing DNA damage. The alteration of the chromatin structure by the compound induced ATM/AKT and PTEN pathway. The stabilized p53 by modulating two signaling pathway induced apoptosis via the activation of Bcl-2 family genes.